Exonyms in Cameroon English: Reinforcing Socio-Political Inclusiveness (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2026)
This study investigated the formation and socio-political significance of place-name exonyms in Cameroon English. It focused primarily on how such naming practices reflect identity negotiation and linguistic inclusiveness in a post-colonial bilingual Cameroon. The study adopted a mixed method design, a research combined documentary analysis and an attitudinal inquiry. The linguistic data were collected from official public service documents, including official communiques, application letters and complaints. And supplemented with informal discussions involving Anglophone Cameroonians in Yaoundé. From these sources, 20 exonym-endonym pairs were identified and classified according to their phonological and orthographic processes. In addition, attitudinal data were obtained through purposive sampling of 273 Francophone respondents from communities whose place names had undergone exonymisation. 154 educated Anglophone respondents were also interviewed on their motivations for English-based naming variants. Quantitative analysis was conducted using percentage distributions, while qualitative interpretations were guided by Tajfel and Turner’s (1979) Social Identity Theory. The findings revealed three dominant exonymic processes in Cameroon English: allophonic variation, diacritic omission, and orthographic simplification. Attitudinal evidence showed broad acceptance of English-based variants when referring to major national locations (over 80% among Francophone respondents and 94% among Anglophones), but resistance emerged when modifications concern local communal names. The study concluded that exonym formation in Cameroon English functions not only as linguistic adaptation but also as a symbolic strategy through which minority speakers negotiate visibility and inclusion within unevenly implemented bilingual policies. The study recommended the dire need for clearer national guidelines on place-name standardisation to balance communicative accessibility with cultural authenticity.
Keywords: Exonyms; Endonyms; Cameroon English; Socio-political inclusiveness; language identity